MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGUNAKAN METODE INKUIRI PADA MATA PELAJARAN IPA DENGAN MATERI BENDA MAGNETIS DAN NON MAGNETIS PADA SISWA KELAS IV SD NEGERI 040445 KABANJAHE TAHUN PELAJARAN 2016/2017 - Jainab Jainab (Universitas Quality, 2018)
The research problem is the low student learning outcomes in the material magnetic and non magnetic objects in the fourth grade elementary school Kabanjahe 040 445. This research was conducted with the aim to improve student learning outcomes in science subjects and non-magnetic material magnetically objects using the method of inquiry. Subjects in the study were students in the fourth grade elementary school Kabanjahe 040 445 Academic Year 2016/2017 amounted to 53 people, consisting of 25 men and 28 women. The research was conducted during the second cycle with the same time, ie 2 x 35 minutes. Each cycle consists of four phases: planning, implementation, observation (observation) and the phase of reflection. Data collection techniques used were observation and tests.Results of votes on the first cycle the average value of 53 students reached 66.79 and the number of students who pass the corresponding KKM as many as 30 people or 57%, while that did not complete there are 23 people or 43%, due to the number of students in classical yet complete then resumed to the next cycle. In the second cycle of the number of students 53 people obtained the number of students who completed their study in accordance KKM many as 47 students or 88.7%, while the incomplete learning there are 6 students or 11.3% with an average of 82.64.